Comparative analysis of fungal and bacterial composition in natural wines and their closest pesticide-treated counterparts - Robin Mesnage; Jérôme Douzelet; Gilles-Eric Seralini (Scientific Reports)
Abstract Fermentation produces diverse consumables like bread, wine, beer, and cheese, with fungi playing a key role. This study sequenced fungal and bacteria DNA from 46 commercial wines, paired by vineyard proximity, harvest time, and grape variety. One in each pair was natural, while the other had pesticide treatments and microbial adjunctions. Bacteria profiles were studied using targeted sequencing of the V3-V4 region of the 16 S rRNA gene while fungal profiles were studied with ITS gene targeted sequencing. Significant variability was observed in the microbial content of these wines. We identified 19 unique fungal species in natural wines, absent in pesticide-treated ones. Some have known health roles. The most abundant was Penicillium jiangxiense in Lot-et-Garonne, known for its antitumor properties. Hyphopichia pseudoburtonii, with notable aromatic properties, was also detected, commonly found in insect and fish microbiota. Antrodia favescens, related to the medicinal Antrodia cinnamomea, was identified in another location, known for its role in Chinese herbal medicine against cancer and metabolic diseases. Ochrocladosporium elatum, recognized for its antioxidant and antibacterial activities, was found elsewhere. Additionally, natural wines exhibited greater bacterial biodiversity, contributing to unique tastes and potential health benefits.